Nepal and the communists : the long march to democracy? - Sujoyini Mandal (2009)
Nepal’s Constituent Assembly elections were postponed for the second time on 22 November 2007. This follows the withdrawal of the Communist Party of Nepal-Maoist (CPN-M) from the government and has exposed the cracks in the arduous road to democracy in Nepal. The absence of governance carries implications for regional security, as shown in the concerns expressed by the United States and India.